A scoping analysis of private sector engagement in humanitarian response in Bangladesh - Ovy, Md. Tanvir Rahman (Brac University, 2020)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.